2022
DOI: 10.1039/d2dt03703c
|View full text |Cite
|
Sign up to set email alerts
|

Deoxygenation of chalcogen oxides EO2 (E = S, Se) with phospha-Wittig reagents

Abstract: In here we present the deoxygenation of the chalcogen oxides EO2 (E = S, Se) with R–P(PMe3), so-called phospha-Wittig reagents. The reaction of DABSO (DABCO⋅2SO2) with R–P(PMe3) (R = Mes*,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Liu and co-workers have recently introduced the class of AuPhos ligands, with the general formula LAu−PR 2 (L = NHC, R = H, Ad, Ph), which could further yield (LAu) 2 PiPr (Au 2 Phos), of which the Rh(acac)CO complex was prepared and showed that Au 2 Phos is a very electron-rich ligand. [38] Compared to the free ligand 1 and Rh complex 4, the P−C NHC distances in 7 (1.836 (7) The short Au•••Au distance (2.9838(4) Å) indicates the presence of an aurophilic interaction through the 1•Rh metallacycle, [39] which is in the same range as those measured in the complex [Me ( Dip TerPO 2 )OPMe 3 [41] 1.4641 (19), 1.4721(17) Å; (PhPO 2 )dmap [42] 1.4752(17), 1.4742( 14)).…”
Section: Resultsmentioning
confidence: 89%
“…Liu and co-workers have recently introduced the class of AuPhos ligands, with the general formula LAu−PR 2 (L = NHC, R = H, Ad, Ph), which could further yield (LAu) 2 PiPr (Au 2 Phos), of which the Rh(acac)CO complex was prepared and showed that Au 2 Phos is a very electron-rich ligand. [38] Compared to the free ligand 1 and Rh complex 4, the P−C NHC distances in 7 (1.836 (7) The short Au•••Au distance (2.9838(4) Å) indicates the presence of an aurophilic interaction through the 1•Rh metallacycle, [39] which is in the same range as those measured in the complex [Me ( Dip TerPO 2 )OPMe 3 [41] 1.4641 (19), 1.4721(17) Å; (PhPO 2 )dmap [42] 1.4752(17), 1.4742( 14)).…”
Section: Resultsmentioning
confidence: 89%
“…(PhPO 2 )­IMe 4 1.4902(10), 1.4855(11) Å) and other Lewis base stabilized dioxophosphoranes (cf. ( Dip TerPO 2 )­OPMe 3 1.4641(19), 1.4721(17) Å; (PhPO 2 )­dmap 1.4752(17), 1.4742(14)). Additionally, the P–C NHC distances (1.8715(19), 1.8660(19) Å) increase significantly upon oxidation, compared to those observed in the free ligand 1 (cf.…”
Section: Resultsmentioning
confidence: 99%
“…We recognized that the use of select phosphorus reagents in initial FLP addition reactions could provide a new P-C bond and yet retain the capacity for further reaction. To this end, we noted the innovative work from the groups of Cummins, 22,23 Protasiewicz [24][25][26][27] and Hering-Junghans [28][29][30][31][32][33] that have described the chemistry of phosphinidene precursors. Herein, we first demonstrate that these species do participate in FLPalkyne addition reactions.…”
mentioning
confidence: 99%